On the Mesoscale Structure of Coronal Mass Ejections at Mercury's Orbit : BepiColombo and Parker Solar Probe Observations - Palmerio, Erika (Institute of Physics Publishing, 2025)
On 2022 February 15, an impressive filament eruption was observed off the solar eastern limb from three remote-sensing viewpoints, namely, Earth, STEREO-A, and Solar Orbiter. In addition to representing the most-distant observed filament at extreme ultraviolet wavelengths—captured by Solar Orbiter's field of view extending to above 6 R⊙—this event was also associated with the release of a fast (∼2200 km s−1) coronal mass ejection (CME) that was directed toward BepiColombo and Parker Solar Probe. These two probes were separated by 2° in latitude, 4° in longitude, and 0.03 au in radial distance around the time of the CME-driven shock arrival in situ. The relative proximity of the two probes to each other and the Sun (∼0.35 au) allows us to study the mesoscale structure of CMEs at Mercury's orbit for the first time. We analyze similarities and differences in the main CME-related structures measured at the two locations, namely, the interplanetary shock, the sheath region, and the magnetic ejecta. We find that, despite the separation between the two spacecraft being well within the typical uncertainties associated with determination of CME geometric parameters from remote-sensing observations, the two sets of in situ measurements display some profound differences that make understanding the overall 3D CME structure particularly challenging. Finally, we discuss our findings within the context of space weather at Mercury's distance and in terms of the need to investigate solar transients via spacecraft constellations with small separations, which has been gaining significant attention during recent years.